Communication and social media management: theory, research and practice - Dennis, Charles; Foroudi, Pantea; Melewar, T. C.; Kitchen, Philip; Melanthiou, Yioula; Papasolonou, Ioanna (My University, 2020)
In the current ongoing scenario of market turbulence, businesses and non-profit organisations (NGOs) are facing new communication challenges from both marketing and corporate perspectives. Societies now look askance at global businesses, consumers are sceptical of promises made and citizens increasingly distrust institutions, governments and political processes. Consumer trust in business practice is at all-time low. Rhetoric without substance is despised everywhere and (probably) only a marked sense of responsibility can lead to new scenarios of success. In response to such a turbulent environment, practitioners and academics need to devise new strategies, models, processes, systems and practices to move their brands forward via effective brand communication.
Keywords: Market turbulence; Businesses; Non-profit organisations; Communication challenges